Theoretical analysis on the micro gas turbine integrated solar farm for power output stabilization - Firdaus, Basrawi; Al-Anati, A. I. M.; Ibrahim, Thamir K.; Mohd Hazwan, Yusof; A. A., Razak; Shaharin Anwar, Sulaiman; Yamada, Takanobu (EDP Sciences, 2018)
Solar farm could not penetrate grid at substantial amount because it could disturb the grid operation due to its fluctuation output. This, the objective of this study is to theoretically analyze the power output stabilization of a solar farm by integration of Micro Gas Turbine (MGT). A 1MW scale of solar farm was first designed according to IEC 60364-5-52:2003, MS281837 and AMBO Chart method. Then, designed solar farm and MGT were modelled and simulated Simulink. In this study, both system need to stabilize power output at 800 kW throughout the year. It was found that it is possible to balance the power output of the solar farm to have constant power output throughout the year at 800 kW. However, all MGTs frequently operated at partial load that decreased their efficiency. Thus, it is possible to solve the solar farm problem with the technique, but further investigation the environmental and economic impact in comparison with a conventional power generation and a solar farm only is needed.